The Agribusiness Innovation Initiative in Ethiopia : Enabling a Climate Smart, Competitive, and Sustainable Agribusiness Sector - Brethenoux, Julia; Aleme, Teklu Kidane; Olafsen, Ellen; Thaller, Jim; Webb, Julian (World Bank, Washington, DC, 2014)
The Agribusiness Innovation Initiative (AII) seeks to contribute to advancing a climate-smart competitive agribusiness sector which will create more jobs and raise incomes for Ethiopians. The AII will contribute toward this objective by identifying innovative growth-oriented entrepreneurs who are pursuing business opportunities based on value addition of agricultural commodities and providing them with a holistic service offering that accelerates their growth and increases their sustainability. In the process of doing so, the AII will engage all stakeholders along the value chain, thus strengthening the innovation and entrepreneurship ecosystem affecting the start-up and growth of innovative agribusiness enterprises. Relatedly, the AII will strive to have a demonstration, or catalytic, effect, encouraging a new generation of entrepreneurs to enter, grow, and advance the industry. The AII will have two groups of beneficiaries. The direct beneficiaries include high growth potential agribusiness entrepreneurs and small businesses. This group includes a high percentage of women. The indirect beneficiaries are the small-holder farmers that supply the raw materials to the enterprises, and the tangential service providers, such as truckers, packaging providers, and others that will benefit from the increased demand generated.